PENGEMBANGAN MEDIA POP UP BOOK PELAJARAN IPAS MATERI METAMORFOSIS, PERUBAHAN BENTUK MAKHLUK HIDUP - Al Frostasya, Ghiska; Kartono, Kartono; Pranata, Rio (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to produce Pop Up Book-Based Learning Media for Science and Science Learning Material on Metamorphosis, Changes in the Shape of Living Creatures for Class III of 36 Pontianak City Public Elementary Schools which has been tested for validity and practic for use. The research method used is Research and Development (R D). The development stages used in this research adopted the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model developed by Dick Carry. The results of research on the development of learning media are learning media based on the results of analysis for class III students, namely media that is interesting, both in terms of appearance and media content. Based on the results of the expert validator's assessment, the Pop Up Book media was declared "very valid" in terms of design, language and material aspects. Based on the results of trials in class III, the learning media developed was also declared "very practical" to use. This level of practicality was obtained from the results of questionnaires given to small and large groups.